2019
DOI: 10.1186/s13722-019-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of alcohol use and illicit substance use in outpatient psychiatric clinics in Sweden: a national survey of clinic directors and staff

Abstract: Background Swedish national guidelines recommend that all health care settings systematically screen patients for alcohol use and illicit substance use. When hazardous use is identified, it should immediately be addressed, preferably through brief interventions (BI). It is well known that the prevalence of alcohol use and illicit substance use among psychiatric patients is high, but it is not known to what extent screening and BI are routinely carried out in such clinics. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…A number of studies have documented that substance use and SUD are under-reported and underdiagnosed in psychiatric treatment settings [24][25][26]. Moreover, a recent Norwegian Board of Health study highlighted the existing deficiencies in specialized mental health services regarding the investigation and examination of patients with possible concurrent SUD [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have documented that substance use and SUD are under-reported and underdiagnosed in psychiatric treatment settings [24][25][26]. Moreover, a recent Norwegian Board of Health study highlighted the existing deficiencies in specialized mental health services regarding the investigation and examination of patients with possible concurrent SUD [27].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the intensive treatment and close monitoring of patients in in-patient treatment allowed clinicians to make a more thorough evaluation of the patients' substance use behaviour, resulting in higher identification rates than in outpatient treatment settings. The underidentification of substance use may also be related to insufficient knowledge of substance abuse issues among clinicians [25] and/or the lower status of working with substance users [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have documented that substance use and SUD are under-reported and underdiagnosed in psychiatric treatment settings [34][35][36]. A recent Norwegian Board of Health study highlighted the existing deficiencies in specialized mental health services regarding the investigation and examination of patients with possible concurrent SUD [37].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A recent Norwegian Board of Health study highlighted the existing deficiencies in specialized mental health services regarding the investigation and examination of patients with possible concurrent SUD [37]. The under-identification of substance use may be related to insufficient knowledge of substance abuse issues among clinicians [35] and/or the lower status of working with substance users [38]. Moreover, the accuracy of reported substance use may depend on the patients' responses when asked about substance use.…”
Section: Strengths and Limitationsmentioning
confidence: 99%